Emotional intelligence in Nursing, models and methods of measurement - Ghofrani Kelishami, Fatemeh; Ashghali Farahani, Mansoureh; Jamshidi Orak, Roohangiz; Arab Ameri, Zahra; Bani Hashemi, Sara; Seyedfatemi, Naimeh (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: Emotional intelligence is one of the most important factors for success in all aspects of life. Emotional intelligence is the ability to recognize emotions in themselves and others, effective management of emotions, the emotions in their motivation and effective communication. Given the importance of the issue and the lack of nursing research in the field of emotional intelligence in Iran, in this article emotional intelligence in nursing, patterns and measurement methods were discussed. Materials and methods: After searching the database Ovid, Science Direct, Scopus, PubMed, SID, Magiran using keywords intelligence, emotional intelligence, nursing students, Information obtained after review of 47 sources. Conclusion: Emotional intelligence can be positive results, such as socio-emotional success, confidence is high, more life satisfaction, health and social commitment to the cause. Patterns of emotional intelligence considered and Different tools have been designed to measure this type of intelligence. Keywords: Intelligence, Emotional Intelligence, Nursing Students